Environmentally appraising different pavement and construction scenarios: A comparative analysis for a typical local road. (January 2015) - Celauro, Clara; Corriere, Ferdinando; Guerrieri, Marco; Lo Casto, Barbara
Graphical abstract: Highlights: An LCA for different scenarios of a typical local road is carried out. Different road construction techniques are analysed with regards to the whole structure. Different percentage of recycled materials are considered for pavement layers. Lime stabilized soils are used as subbase material or for construction of the embankment. The analysis proves a significant reduction of energy consumption and pollutant emissions. Abstract: The aim of this work is to carry out a comparative analysis of environmental impacts for different scenarios of a typical local road. Life Cycle Assessment (LCA) is the modeling tool used to quantify and characterize comparative environmental impacts. In carrying out this specific application of the LCA, different road construction techniques were considered with regards to the whole structure and compared in order to identify the best alternative in terms of environmental sustainability. So far, in fact, typical LCA frameworks of roads have focused on recycled materials for pavement layers only, thus neglecting study of the materials used in the embankment or in the subgrade. In this study, these materials were included too, in order to prove the environmental benefit of using a sustainable technique such as in situ stabilization of fine soils with lime (typically dumped clayey soils) in order to reduce the need for virgin material for embankment and subgrade construction. When using different percentages of recycled materials (such as reclaimed asphalt pavement – RAP) in the bituminous layer or in the foundation, the analysis of the functional unit studied shows a significant reduction of energy consumption and pollutant emissions mainly due to transportation of materials involved, in this way increasing the environmental performance of the road. Another important consideration is that the use of fine soils stabilized with lime "in situ", instead of dumping it, not only is a good technical solution for improving soil mechanical properties, but it also produces a reduction of energy consumption and of pollutant emissions. It is noticeable that this technique results in a significant reduction of pollutant emissions due the transportation of involved materials, increasing the environmental performance of the road.